Characteristics of familiar agriculture in a municipality at South of Brazil: main illnesses, care and use of medicinal plants (Research, Society and Development, 2021)
Objectives: Characterize the agricultural families and identify the most prevalent health diseases, as well as identify the practice of using medicinal plants in health care. Methods: Descriptive epidemiological study, cross-sectional, with data collection by household survey. Results: 104 households surveys were applied. Predominance of women (71.2%, n=74), with a partner (71.2%, n=74) and mean age of 49.2 (±16.36) years old. 65.4% of the interviewed population declares to have health issues, highlighting heart problems (31.5%), autoimmune (27%), respiratory diseases (11.7%), and mental health (10.8%). Using medicinal plants is perceived in 79.8%, as coadjuvant on illnesses treatments. Conclusion: Using medicinal plants, in rural populations, is a common action and, generally, the acknowledgment about its use is transmitted by family generations. The results of this study may contribute to propose actions that involve rural development and health to the studied community, or others, particularly similars, intending to develop actions aimed to health promotion to agricultural people in vulnerable situations, to care and prevention of diseases.